Histologic and histomorphometric study of bone repair around short dental implants inserted in rabbit tibia, associated with tricalcium phosphate graft bone - Marlice Azoia Lukiantchuki Barbosa; Liogi Iwaki Filho; Lilian Cristina Vessoni Iwaki; Maria Raquel Marçal Natali; Wilton Mitsunari Takeshita; Sérgio Sábio (Acta Scientiarum. Health Sciences, 2014)
The use of short dental implants represents one way to overcome this limitation, in association with bone grafting procedures. Tricalcium phosphate-based grafts are among those widely used. The purpose of this study was to assess the biocompatibility of this biomaterial in the coverage of bone defects around short dental implants. Ten New Zealandrabbits were used in this study, each animal received 4 implants, two were placed in the right tibia region (control group) and two in the left tibia region (test group). Forty implants were used, with 4mm diameter and 6mm length. For the control group, holes 6 mmdeep were made, and the implants were then inserted at the level of bone tissue. In the control group, the implants of 6 mmin length were inserted to its full length, while in the test group, the same implant was inserted up to 4 mmand left exposed 2 mm. These 2 mmexposed were coated with a bone substitute of tricalcium phosphate and a collagen membrane. After three months, the animals were prepared for histomorphometric analysis, which showed that the control group had a higher number of osteoblasts per μm2 than the test group (p < 0.001). It was concluded that under these experimental conditions, tricalcium phosphate showed tissue biocompatibility and osteoconductive potential.